Tone, the driving force in Qaisar Aminpour's Ashura Elegies - Seyed Mehdi Mousavi nia; Gholamreza Kafi (مطالعات زبانی و بلاغی)
Elegy has always been a popular genre, especially in poetry. This type of composition, due to its special subject matter, has special features and crafts to convey the message and relate to the audience. Composing poetry about Ashura, as one of the manifestations of love for the family of Prophet Mohammad (PBUH), has especially has received more attention after the victory of the Islamic Revolution, and many poets have experimented in this field. In this relation, the poems of Qaisar Aminpour as one of the poets of this group received much attention. In his Ashura poems, a cherishing and warm verbal language flows along with the clarity that can be seen in his other poems. In the present study, the element of tone was studied with respect to the sincere and indirect transmission of the message of sorrow and grief. Considering its importance in conveying the implicit message of the text, it was revealed that the poet has observed the tone and subject matter of the poem in choosing the form. He has considered the rhythm and its propriety with the sad atmosphere of the poem in order to choose the metrical pattern. He has also used rhyme and rhythm and their phonetic compatibility as an important principle to align with the audience. Aminpour has also made use of figurative language, especially metaphors to depict the poetic landscapes the musicality of sounds and the magic of the proximity and contiguity of letters as a style to create a more emphatic tragic tone in Ashura poems.